Fa'âliyah Istikhdâm Al-Lughah Al-'Arabiyah fî Tadrîs Al-'Ulûm Al-Syar'iyyah li Iktisâb Mahàrah Al-Kalâm 'alâ Dhou' Al-Madkhal Al-Takâmulî li Al-Lughah wa Al-Muhtawa lil Fashl Al-Sâbi' bi Ma'had Muhammadiyah Al-Islâmî li Al-Tafaqquh fî Al-Dîn Yogyakarta - Yulianda, Ardinil; Moh Mahbub (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2024)
أهداف هذا البحث هي (1) وصف استخدام اللغة العربية في تدريس العلوم الشرعية على ضوء CLIL . (2) معرفة فعالية استخدام اللغة العربية في تدريس العلوم الشرعية لاكتساب مهارة الكلام على ضوء CLIL. (3) معرفة أيهما أكثر فعالية بين استخدام اللغة العربية في تدريس العلوم الشرعية على ضوء CLIL و تدريس العلوم الشرعية باستخدام التعلم التقليدي لاكتساب مهارة الكلام. يستخدم الباحث في هذا البحث المنهج الكمي. وأسلوب لجمع البيانات في هذا البحث هي الملاحظة، المقابلة، التوثثيق، والاختبار. وعينة مجتمع البحث هؤلاء طلاب وطالبات الفصل السابع. نتيجة هذا البحث (1) إن استخدام اللغة العربية في تدريس العلوم الشرعية على ضوء CLIL يسير في خمس خطوات وهي إعداد الدرس، افتتاح الدرس عرض الدرس التدريبات التقويم. وهذه الخطوات تشتمل على جميع المبادئ الأربعة في المدخل التكاملي للغة والمحتوى (CLIL) وهي : المحتوى الاتصال، المعرفة، والثقافة. (2) وفقا على مقارنة بين نتائج الاختبار القبلي والاختبار البعدي للطائفة الضابطة والطائفة التجربة، علم الباحث أن استخدام اللغة العربية في تدريس العلوم الشرعية على ضوء المدخل التكاملي والمحتوى (CLIL) فعالية لاكتساب مهارة الكلام لدى طلاب الصف السابع، . ويؤكد كذالك نتيجة تاء الحساب في هذا البحث (4,60) أكبر من نتيجة (t-table)( 2,72). (3 وبهذه الدلائل يشير إلى أن تدريس العلوم الشرعية باستخدام اللغة العربية على ضوء CLIL أكثر فعالية مقارنة بتدريس العلوم الشرعية باستخدام التعلم التقليدي لاكتساب مهارة الكلام The aim of this research is (1) to describe the use of Arabic in teaching sharia sciences using the CLIL approach. (2) Knowing the effectiveness of using Arabic in teaching sharia sciences to acquire speaking skills using the CLIL approach. (3) Knowing which is more effective between using Arabic in teaching sharia sciences using the CLIL approach and teaching sharia sciences using traditional learning to acquire speaking skills. In this research, researchers used quantitative methods. Data collection methods in this research are observation, interviews, documentation and tests. The research population sample was seventh grade male and female students, and twenty-one samples were taken for the control group and twenty-two for the experimental group. The results of this research are (1) The use of Arabic in teaching sharia sciences using the CLIL approach takes place in five steps, namely preparing the lesson, opening the lesson, presenting the lesson, practice and evaluation. These steps cover all four principles in the Integrated Approach to Language and Content (CLIL): content, communication, knowledge, and culture. (2) Based on a comparison of the pre-test and post-test results of the control group and the experimental group, the researcher knows that the use of Arabic in teaching sharia sciences using the (CLIL) approach is effective in acquiring seventh grade students' speaking skills. This also confirms that the t_count (t_o) calculation results in this study (4.60) are greater than the results (t-table) (2.72). (3) This evidence shows that teaching sharia sciences using Arabic with a CLIL approach is more effective than teaching sharia sciences using traditional learning to acquire speaking skills.